Pertanggungjawaban Pidana Pelaku Cloning Website Berbasis Perjudian Online (Studi Kasus Putusan Nomor 2014/Pid.Sus/2024/PN Tng) - Pardamean Harahap; Diana Puspitasari (Jurnal Hukum Lex Generalis, 2025)
This study aims to analyze the criminal liability of perpetrators of cloning websites containing online gambling and to assess the conformity of Decision Number 2014/Pid.Sus/2024/PN Tangerang with the principles of legality and fault. The study uses a normative juridical method with a legislative and case approach. The results of the study show that website cloning is not explicitly regulated in the ITE Law, Kominfo technical regulations, or the new Criminal Code, so that the application of Article 27 paragraph (2) of the ITE Law is extensive. The conclusion of the study confirms the existence of a de jure and de facto gap that has the potential to result in disproportionate punishment. This study recommends the establishment of specific regulations to ensure legal certainty and protection.